Unity power factor correction circuit based on boost-buck DC-to-DC converter with coupled inductance - Milanovič, Miro (Informacije MIDEM, 1992)
The unity power factor correction circuits are nowadays becoming one of the most important requirements for all power electronic rectifiers (equipment). The idea of using coupled inductance in a single phase diode rectifier power factor correction circuits and the influence of the coupling factor on the current ripple are discussed.
Keywords: coupled inductance; DC to DC converters; enofazna vezja; enosmerni presmerniki; faktor moči; korekcija faktorja moči; močnostna elektronika; power electronics; power factor; power factor correction; single phase circuits; sklopljena induktivnost